Toward a relational biodiversity economics: Embedding plural values for sustainability transformation - Jasper O. Kenter; Rachel Carmenta; Michael Christie; Hywel Griffiths; Eberechukwu Ihemezie; Adrian Martin; M. Teresa Gomez-Osorio; Unai Pascual; Christopher M. Raymond; Kyriaki Remoundou; Ruth Waters (Proceedings of the National Academy of Sciences, 2025)
The prioritization of market over nonmarket values of nature is a key driver of the global biodiversity crisis. Recognizing nature’s diverse values in decisions is a fundamental lever for sustainability transformation. While economic valuation of nature has a long history, it has struggled to recognize the full suite of nature’s values, particularly the broad, relational, intrinsic, and shared values reflecting the complexity of human–nature relationships. We explore opportunities to expand the consideration of values within the economics of biodiversity by reviewing conventional and heterodox economic approaches. We argue that integrating pluralistic values requires a relational biodiversity economics that transcends people–nature dualism and seeks the flourishing of life. We synthesize foundations for such a paradigm in relation to worldviews, values, value indicators, and life frames. Our perspective transcends the dominant economic framing of nature as a passive, largely substitutable asset, to also consider nature as place, self, and harboring agency. This helps to overcome the limitations of conventional economic assumptions, better reflects peoples’ lived experiences, and supports transformations toward more just and sustainable futures.